Prevalence of sepsis among adults in China: A systematic review and meta-analysis - Lei, Siyuan; Li, Xuanlin; Zhao, Hulei; Xie, Yang; Li, Jiansheng (Frontiers in Public Health, 2022)
Background Sepsis is a major public health problem that cannot be ignored in China and even in the world. However, the prevalence of sepsis in Chinese adults varies among different studies. Objective To evaluate the prevalence of hospital-wide sepsis and intensive care unit (ICU) sepsis in Chinese adults. Methods PubMed, EMBASE, Cochrane Library, Web of science, China National Knowledge Infrastructure, Chinese biomedical literature service system, Wanfang Database, and VIP databases were systematically searched for studies on sepsis in China published before March 2, 2022. Random effects model was used to calculate pooled prevalence estimates with 95% confidence interval. Subgroup and sensitivity analyses were performed to address heterogeneity. Funnel plots and Egger's test were used to assess the publication bias. Results Overall, nine observational studies involving 324,020 Chinese patients (9,587 patients with sepsis) were analyzed. Four hospital-wide studies involving 301,272 patients showed pooled prevalence and mortality of 3.8% (95% CI: 2.9–4.7%, I2 = 99.9%) and 26% (95% CI: 16–36%, I2 = 98.0%), respectively. Five studies of ICU sepsis involving 22,748 patients presented pooled prevalence and mortality of 25.5% (95% CI: 13.9–37.0%, I2 = 99.8%) and 40% (95%CI: 34–47%, I2 = 95.9%), respectively. Subgroup analysis of sepsis in ICUs revealed that the pooled prevalence was higher among males [17% (95% CI 9–24%, I2 = 99.6%)], in lung infections [66% (95%CI: 54–77%, I2 = 98.7%)], and Gram-negative bacteria infections [37% (95%CI: 26–47%, I2 = 98.3%)]. The pooled prevalence of sepsis, severe sepsis and septic shock was 25.5% (95%CI: 13.9–37.0%, I2 = 99.8%), 19% (95%CI: 9–28%, I2 = 99.6%), and 13% (95%CI: 7–19%, I2 = 99.2%), respectively. Conclusions Sepsis is prevalent in 25.5% of ICU patients in China, and sex, sepsis severity, infection site, causative microorganism, and infection type are significant influencing factors. Larger trials are needed to evaluate the prevalence of sepsis in China, which may help the development of global strategies for sepsis management. Systematic review registration PROSPERO, identifier: CRD42022314274.